Device Evaluation, Treatment, and Explantation Recommendations (DETER): Review and Best Practices for Managing Neuromodulation Device Infections - Pritzlaff SG; Goree JH; Dare RK; D’Souza RS; Lee DW; Dudas AA; Kalia H; Orhurhu V; Singh N; Hagedorn JM; Mousavi A; James W; et al. (Journal of Pain Research)
Scott G Pritzlaff,1 Johnathan Heck Goree,2 Ryan Keith Dare,3 Ryan S D’Souza,4 David W Lee,5 Andrew Adams Dudas,6 Hemant Kalia,7 Vwaire Orhurhu,8 Naileshni Singh,1 Jonathan Michael Hagedorn,4 Arman Mousavi,9 Whitney James,10 Michael Spencer Leong,11 Kathleen W Meacham,12 Amitabh Gulati,13 Samir J Sheth,14 Israel Pena,15 Jarna R Shah,2 Melissa Zhu Murphy,16 Sara E Nashi,17 Morad Nasseri,9 Andrew M Khoury,18 Michael J Dorsi,19 Steven Michael Falowski,20 Erika A Petersen,21 Nestor D Tomycz,22 Sayed Wahezi,23 Krishnan V Chakravarthy,24 Jason E Pope,25 Michael E Schatman,26,27 Kasra Amirdelfan,28 Dawood Sayed,29 Timothy Ray Deer30,31 1Anesthesiology and Pain Medicine, University of California, Davis, Sacramento, CA, USA; 2Anesthesiology, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 3Internal Medicine/Division of Infectious Diseases, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 4Anesthesiology and Perioperative Medicine, Mayo Clinic, Rochester, MN, USA; 5Fullerton Orthopedics, University of California, Fullerton, CA, USA; 6Mays and Schnapp Neurospine and Pain, Memphis, TN, USA; 7Center for Research & Innovation in Spine & Pain (CRISP), Rochester, NY, USA; 8Anesthesiology, University of Pittsburgh Medical Center, Williamsport, PA, USA; 9Neurology and Interventional Pain Medicine, Boomerang Healthcare, Walnut Creek, CA, USA; 10Neurosurgery, James-Marco Health, Prescott, AZ, USA; 11Anesthesiology, Perioperative and Pain Medicine, Stanford University, Stanford, CA, USA; 12Veteran’s Affairs Healthcare System, Saint Louis, MO, USA; 13Anesthesiology and Critical Care, Memorial Sloan Kettering Cancer Center, New York, NY, USA; 14Neurosciences, Sutter Health, Roseville, CA, USA; 15Pain Management, Lakeside Physicians, Granbury, TX, USA; 16North Texas Orthopedics and Spine Center, Dallas Fort Worth, TX, USA; 17Interventional Pain & Spine, TriHealth, Cincinnati, OH, USA; 18Advanced Spine and Pain Specialists, The Woodlands, TX, USA; 19Neurosurgery, University of California Los Angeles, Los Angeles, CA, USA; 20Neurosurgery, Neurosurgical Associates of Lancaster, Lancaster, PA, USA; 21Neurosurgery, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 22Neurological Surgery, Allegheny Health Network, Pittsburgh, PA, USA; 23Rehabilitation Medicine, Montefiore Medical Center, New York, NY, USA; 24Anesthesiology and Pain Medicine, Solaris Research Institute, San Diego, CA, USA; 25Evolve Restorative Center, Santa Rosa, CA, USA; 26Department of Anesthesiology, Perioperative Care and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 27Department of Population Health - Division of Medical Issues, NYU Grossman School of Medicine, New York, NY, USA; 28Clinical Research, Boomerang Healthcare, Inc., Walnut Creek, CA, USA; 29Anesthesiology, The University of Kansas Health System, Kansas City, KS, USA; 30Anaesthesiology and Pain Medicine, West Virginia University School of Medicine, Charleston, WV, USA; 31Pain Services, WVU Medicine – Thomas Hospitals, Charleston, WV, USACorrespondence: Scott G Pritzlaff, University of California, Davis, 4860 Y Street, Suite 3020, Sacramento, CA, 95817, USA, Email spritzlaff@ucdavis.eduAbstract: Infections related to neuromodulation devices such as spinal cord stimulators (SCS) and intrathecal pumps (ITPs) present complex challenges due to potential complications such as localized infections, deep infections, sepsis, and neurological injury. Prompt diagnosis requires patients and providers to be educated on wound management and sepsis symptoms for immediate medical attention. Antibiotic therapy and duration vary based on infection severity, with deep infections often requiring device removal despite recent improvements in salvage rates with aggressive initial intervention. Deep infections necessitate timely diagnosis through imaging modalities such as magnetic resonance imaging (MRI) or computed tomography (CT), followed by device removal and culture-guided antibiotic therapy, often in collaboration with infectious disease specialists and spine surgeons. ITP infections pose similar challenges along with the risk of meningitis and may require careful management of medication withdrawal symptoms during emergent pump removal. Lab monitoring may aid treatment assessment, although negative cultures can occur due to post-antibiotic exposure. Postoperative recommendations stress standardized guidelines, patient education, and vigilant surveillance, with close follow-up crucial for early infection detection and intervention. Managing device-related infections demands a multi-specialty approach to minimize complications and optimize outcomes. This paper outlines best practices for diagnosing, managing, and treating neuromodulation device infections, focusing on guiding clinical decision-making from the onset of infection through treatment and potential reimplantation.Keywords: spinal cord stimulation, intrathecal pumps, procedure complications, infection control, surgical site infection